THE STRATEGY FOR OVERCOMING EARLY MARRIAGE IN WAJO REGENCY - Yuyun Ardianti; Muh Nur Yamin; Andi Cudai Nur; Nina Agustina (Universitas Negeri Makassar, 2026)
This study aims to determine the Strategy for Overcoming Early Marriage in Wajo Regency. This research includes descriptive qualitative research with data collection techniques through observation, interviews and documentation. Data analysis techniques using SWOT analysis.The results showed that the Early Marriage Response Strategy in Wajo Regency has not been overcome because there are still challenges in overcoming early marriage, although there have been efforts to overcome this, this is evidenced based on the indicators of Travis Hirchi's (2005) overcoming theory, namely: 1) Attachment (Affection), 2) Commitment (Responsibility), 3) Involvement (Involvement) 4) Believe (Trust). That in general, the Strategy for Overcoming Early Marriage in Wajo district is still not optimal due to various challenges that still exist, the main challenge is the lack of public awareness of the impact of early marriage and the existence of social and cultural norms supporting early marriage,By using SWOT analysis, the results obtained from this study are in quadrant IV or WT (Weakness-Threats) strategy, it is necessary to have firmer regulations and clear sanctions for violators of regulations related to early marriage, these sanctions are in the form of fines, criminal penalties in accordance with applicable policies in Wajo Regency.